Outdoor education : methods and strategies - Bates, Timothy, ....-; Gilbertson, Ken, ....-; McLaughlin, Terry, ....- (Champaign : Human Kinetics, 2006)
Outdoor Education: Methods and Strategies will show students how to use physical, cognitive, and affective methods to teach lessons in different settings to different audiences; link educational theories to teaching methods and choose the best method for each setting; and implement strategies with easy-to-use forms and lesson plans. Outdoor Education: Methods and Strategies provides all the necessary information and tools for teaching outdoor education. It applies educational theories to outdoor teaching methods and helps educators choose the instructional strategy that will work best for their audience, whether they're in a school, nature center, adventure center, camp, environmental learning center, government agency, or university. This text includes the following features: Easy-to-use forms for designing, implementing, and evaluating outdoor lesson plans; Six highly detailed sample lesson plans, representing a variety of settings for different age groups and abilities and using physical, cognitive, and affective methods; Teaching tips, real-life case studies, and interactive exercises to apply concepts in each chapter. Outdoor Education: Methods and Strategies contains practical lesson plans and examples that go beyond the normal scope of a text. It includes key concepts, objectives, and summaries for each chapter, and it presents an extensive set of educational methods and applications to foster optimal learning. (Bron: www.humankinetics.com)